Health-seeking behaviour and empowerment dimensions among married women with special reference to Kudumbashree units - Athira Venugopal; Sibin Mathew Medayil (International Journal Of Community Medicine And Public Health, 2026)
Background: The background of this study was about the health seeking behaviours of married women who are the active members of Kudumbashree units. Health seeking behaviour of an individual refers to the actions taken by them to prevent, cure or reduce the risk of a disease to maintain good health. The measures through which they seek medical care for better health outcomes are refereed as health care services. Methods: A cross-sectional quantitative study was conducted using a structured questionnaire administered to assess the health seeking behaviours of married women in Kudumbashree units in Ernakulam District. Simple random procedure was employed to recruit the participants for the study. Results: Health-seeking behaviour was largely positive, with a majority of women that is over 60% of women seeking treatment promptly and primarily depending on government hospitals due to affordability, proximity and trust. Kudumbashree participation significantly strengthened health awareness and autonomy, with more than two-thirds of the respondents reporting improved health knowledge and confidence in taking health-related decisions and regular meeting attendance showing a strong association with health care utilisation. Conclusions: Financial constraints were the most prominent barrier, reported by over half of the respondents, often combined with transport difficulties and lack of awareness, while around one-third of women avoided healthcare for certain conditions due to stigma. Kudumbashree functioned as an effective empowerment platform, with a large majority indicating greater confidence in discussing health issues and increased participation in household health-related decision-making.